Neuropeptide Y prevents nucleus pulposus cells from cell apoptosis and IL‑1β‑induced extracellular matrix degradation - Sun, Kaiqiang (Cell Cycle, 2021)
Intervertebral disc degeneration (IDD) is characterized by excessive inflammatory reaction, and neuropeptide Y (NPY) was reported to have anti-inflammatory effect. However, the effect of NPY on NP cells has not been investigated up to date. This study aimed to clarify the role of NPY on the process of IDD. Fourteen fresh human lumbar intervertebral discs were harvested, and degeneration-related proteins were examined. Pfirrmann grading system was used to evaluate IDD. Rat nucleus pulposus (NP) cells were used to investigate the effect of NPY on the proliferation, apoptosis, and extracellular matrix (ECM) in NP cell induced by IL-1βin vitro. The expression levels of NPY and its receptors (type 1 receptor, Y1R, and type 2 receptor, Y2R) were detected via immunohistochemical analysis, western blot, and quantitative real-time polymerase chain reaction (qRT-PCR). Cell viability and proliferation were explored using cell counting kit-8 assay, western blot, and immunofluorescence analysis. Cell apoptosis was investigated by Hoechst staining, JC-1 Staining, annexin V-FITC/PI double staining, and western blot. The secretion of NPY from NP cells was determined via enzyme-linked immunosorbent assay (ELISA). The expression of anabolic and catabolic gene was analyzed by qRT-PCR, western blot, immunofluorescence analysis, and ELISA. The expression of Y2R was significantly increased in both human degenerative intervertebral discs and IL-1β-induced NP cells. Although no positive results for NPY indicated by western blot both in vivo and in vitro, ELISA results demonstrated that the secretion of NPY from NP cells was increased by low-concentration IL-1β, but was decreased when the concentration of IL-1β was 30 ng/ml and above. In addition, NPY could promote NP cells proliferation and protect NP cells against IL‑1β‑induced apoptosis via suppressing mitochondrial-mediated apoptosis pathway. What’s more, NPY can suppress the expression of catabolic gene and ameliorate IL-1β- induced matrix degeneration in NP cells. In conclusion, NPY could promote NP cell proliferation and alleviate IL‑1β‑induced cell apoptosis via mitochondrial pathway. In addition, NPY can suppress the expression of ECM‑catabolic proteinases and ameliorate IL-1β- induced ECM degeneration in vitro.